Association of intrapatient tacrolimus variability and concentration-to-dose ratio with outcomes in pediatric kidney transplantation - Baghai Arassi, Maral; Fisch, Nora; Feißt, Manuel; Krupka, Kai; Höcker, Britta; Fichtner, Alexander; Kanzelmeyer, Nele; König, Jens; Melk, Anette; Oh, Jun; Pape, Lars; Weber, Lutz T.; et al. (Pediatric nephrology, 2025)
Background: Data on the relevance of tacrolimus intrapatient variability (TacIPV) and concentration-to-dose ratio (C/D ratio) as an approximation of tacrolimus metabolism for predicting outcomes in pediatric kidney transplant (pKTx) recipients are scarce. Methods: We conducted a multicenter retrospective study of 255 pKTx recipients from the CERTAIN registry. TacIPV was quantified as the coefficient of variation (CV%) during months 6–12 post-transplant. In addition, the C/D ratio, corrected for body surface area, was calculated for the first 6 months post-transplant. Cutoffs were determined by minimization of log-rank P values: 23% for TacIPV and 1.0 for C/D ratio. Rejection episodes were classified according to the Banff criteria in the period following marker quantification. Results: A total of 13,159 tacrolimus trough blood levels were analyzed, with a median of 52 (IQR, 41–63) measurements per patient. High TacIPV (> 23%) during months 6–12 post-transplant was associated with an increased risk of rejection beyond 12 months post-transplant (hazard ratio (HR) 1.04, 95% CI 1.01–1.06, P = 0.002; Kaplan–Meier analysis P = 0.002). Similarly, a low C/D ratio (< 1.0), i.e., rapid tacrolimus metabolism, during the first 6 months was associated with a higher risk of rejection between months 6 and 12 (inverse HR 3.13, 95% CI 1.01–9.09, P = 0.04; Kaplan–Meier analysis P = 0.011). Conclusions: This largest to date multicenter study determines pediatric-specific cutoff values for TacIPV and tacrolimus C/D ratio as a predictive marker for graft rejection. Patients with these risk factors should be closely monitored and their immunosuppressive therapy adjusted accordingly.